(untitled) (LACCEI, 2024)
In this research, it was examined the potential of whey for the optimization of biogas production by anaerobic co – digestion with cow slurry. It was used a two-component multifactorial – design, where it was studied four batch type - biodigesters of 4 liters in laboratory scale with different whey concentrations (0%, 10%, 30%, 50%) and dilute cow dung in relation 1:1.5, each one in three replications. The experimentation was performed under temperature control of 35°C±2°C pH control between 6.4 to 6.9 by addition of NaOH 3N with an average of 7% of total solids and a holding time of 35 days. Below these conditions, the 2nd biodigester with 10% of whey, it was the one which generate the largest amount of biogas with 37.9 liters in total the 3rd biodigester, with 30% of whey generates 24.2 liters of biogas and the 4th biodigester, with 50% of whey generates 14.5 liters. Total solids reduction in biodigesters were 38.5%, 43.4%, 40.2% and 27.6% respectively. It was used Gompertz model, that allowed to found high grades of correlation grades oscillating between 86.295% y 94.268%. Therefore, it can be established, that the use of whey duplicates the biogas production until 52% and sets a limit of 30% (v/v) to obtain a good biogas production in batch type biodigesters.